Collaborative Adaptive Governance Model in Sustainable Natural Resource Management in the Era of Climate Uncertainty - Koetosada Voingpuhakdy (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study aims to examine the role of collaborative adaptive governance in promoting sustainable natural resource management under conditions of climate uncertainty in Laos. Specifically, it investigates the effects of collaborative governance and climate uncertainty on adaptive governance, the influence of adaptive governance on sustainable natural resource management, and the mediating role of adaptive governance within these relationships. Subjects and Methods: A quantitative research design was employed using a survey of 320 stakeholders representing government agencies, local governments, non-governmental organizations, community organizations, and academic institutions involved in natural resource governance in Laos during 2025. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The analysis included measurement model evaluation, structural model assessment, hypothesis testing, and mediation analysis. Results: The findings reveal that collaborative governance significantly strengthens adaptive governance, while climate uncertainty positively encourages institutional adaptation. Adaptive governance exerts the strongest direct effect on sustainable natural resource management and partially mediates the relationships between collaborative governance, climate uncertainty, and sustainability outcomes. These results support Collaborative Governance Theory, Adaptive Governance Theory, and Social-Ecological Systems Theory, demonstrating that institutional learning, stakeholder collaboration, and governance flexibility enhance environmental resilience and improve resource management effectiveness under uncertain climatic conditions. Conclusions: The study concludes that adaptive governance is the key institutional mechanism translating collaborative governance and climate uncertainty into sustainable natural resource management. Strengthening collaborative institutions, adaptive leadership, and cross-sector coordination should therefore become strategic priorities for enhancing environmental governance and long-term sustainability in Laos.